Peningkatan iptek guru TK melalui penggunaan aplikasi zoom untuk pembelajaran berbasis daring - Indrawatiningsih, Nonik; Hakim, Luthfi (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The role of technology (science and technology) is currently very much needed as a means of conducting online learning. One of the technologies that can be applied in bold learning is the Zoom Meeting Cloud application. The purpose of this service is to provide training to kindergarten teachers in operating the Zoom Cloud Meeting application as a bold learning tool. The method used is in the form of training. The subject of the study are 6 orders of people and is a kindergarten teacher. The performance indicator in the implementation of this service program is 70% of participants can operate the Zoom Cloud Meeting application. Based on the results of the training, it shows that the training participants can be categorized into 2, namely participants who succeed in achieving 5 indicators (100%) with 2 participants and participants who reach 4 indicators (80%) with 4 participants in using the Zoom Cloud Meeting application. From this training the participants were greatly helped because the previous participants had not been able to operate the Zoom Cloud Meeting application but after the training participants were able to run the Zoom Cloud Meeting application.